How Does Fitness Level Affect Physical Education, Sports, And Health Student Learning Achievement - April Yesaya Sipayung; Aliman (Jurnal Ilmu Keolahragaan Undiksha, 2024)
Formal education in schools is very important for developing the quality of human resources. Still, students' lack of physical fitness often hampers efforts to improve the quality of education. Lack of physical fitness hurts student learning achievement in Physical Education, Sports, and Health (Penjasorkes) subjects. This study aims to analyze the level of physical freshness, physical fitness learning achievement, and the influence of physical freshness level on the learning achievement of junior high school students. This type of research is descriptive quanitative research. The population used is all male students with totaling 348 students and aged between 13 and 15 years. The sampling technique uses purposive sampling techniques, namely sampling, by selecting samples according to certain objectives totaling 40 students. Data collection methods and instruments in this study used TKJI tests aged 13-15 years consisting of (1) 50 meter sprint, (2) hanging body lift for 60 seconds, (3) lying down for 60 seconds, (4) jumping upright, (5) running 1000 M, and PE achievement data through the end of semester report card. After the data was collected, it was analyzed using the Pearson correlation analysis method. The results showed that students' physical fitness level was in the moderate category, and the students' learning outcomes were in the high category. Therefore, it can be concluded that the level of physical fitness significantly influences student learning achievement. This study is expected to positively contribute to improving learning achievement and student well-being at all levels of education.